2013
DOI: 10.1016/j.biopsych.2012.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Allopregnanolone Elevations Following Pregnenolone Administration Are Associated with Enhanced Activation of Emotion Regulation Neurocircuits

Abstract: Background The neurosteroid allopregnanolone is a potent allosteric modulator of the GABA(A) receptor with anxiolytic properties. Exogenous administration of allopregnanolone reduces anxiety, and allopregnanolone blockade impairs social and affective functioning. However, the neural mechanism whereby allopregnanolone improves mood and reduces anxiety is unknown. In particular, brain imaging has not been used to link neurosteroid effects to emotion regulation neurocircuitry. Methods To investigate the brain b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
70
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(84 citation statements)
references
References 82 publications
13
70
0
1
Order By: Relevance
“…Third, during an emotional appraisal task in healthy men treated with pregnenolone, increased allopregnanolone plasma levels were accompanied by altered connectivity between the medial PFC and the amygdala, components of a circuit implicated as dysfunctional in depression (Sripada et al, 2013). Fourth, postmortem studies observed decreased 5α-reductase mRNA expression in the PFC of depressed men and women compared with non-depressed controls (Agis-Balboa et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Third, during an emotional appraisal task in healthy men treated with pregnenolone, increased allopregnanolone plasma levels were accompanied by altered connectivity between the medial PFC and the amygdala, components of a circuit implicated as dysfunctional in depression (Sripada et al, 2013). Fourth, postmortem studies observed decreased 5α-reductase mRNA expression in the PFC of depressed men and women compared with non-depressed controls (Agis-Balboa et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…More recent work has suggested that pregnenolone and its metabolites modulate functional connectivity in the human amygdala (Sripada et al, 2014) and enhance activation of neurocircuits pertinent to mood and emotions (Sripada et al, 2013). Clinical trials suggest that pregnenolone and its derivatives, such as allopregnanolone, have potential in treating schizophrenia (Marx et al, 2009;Ritsner et al, 2010;Zorumski et al, 2013b).…”
Section: Introductionmentioning
confidence: 99%
“…A small study that included both unipolar and bipolar depressed patients suggested improvement in depressive symptoms with pregnenolone (100 mg/day) as compared with placebo (Osuji et al, 2010). Given these data, pregnenolone and other neurosteroids have been suggested as potential therapeutic targets for neuropsychiatric disorders (Sripada et al, 2013;Torrey and Davis, 2012;Zorumski and Mennerick, 2013a;Zorumski et al, 2013b).…”
Section: Introductionmentioning
confidence: 99%
“…In support of the hypothesis that allopregnanolone and pregnanolone have anxiolytic properties, two small studies suggest that the plasma concentrations of pregnenolone sulfate, a precursor of these steroids, is lower in males with generalized social phobia or GAD (Semeniuk et al, 2001;Heydari and Le Mellédo, 2002). Administration of pregnenolone is associated with an increase in allopreganolone and reduced activity in the amygdala and insula, as well as a reduction in self-reported anxiety (Sripada et al, 2013) (Fig. 10).…”
Section: F Neuroactive Steroids As Neuromodulators Of Transmissionmentioning
confidence: 85%